Uso de reguladores de crescimento em plantas e estacas de aceroleira (Malpighia emarginata D.C.) - Morais, Rafael Ramos de (2018)
The barbados cherry tree is a tropical fruit tree highlighted by the high content of vitamin C in its fruits. In search of cultivars that have fruits with higher content of vitamin C and better mechanical resistance, the breeding programs of the culture have been promoted. In order to maintain the agronomic characteristics of each clone, vegetative propagation is indicated. However, the barbados cherry genotypes present distinct and ununiform rooting potential. In this context, the objective of this study was to evaluate the effect of treatment matrix plant with zinc and ethephon on rooting of cuttings acerola, under doses of IBA. Two experiments were carried out, one with the cultivar BRS 235 Apodi and the another elite lineage in final phase of breeding program. In both, a completely randomized design was used, in factorial 3x2x4, whose factors were treatment of stock plant (without treatment, zinc, and ethephon), cuttings types (herbaceous and semi-hardwood) and doses of IBA (0; 1000; 1500; 2000 mg.L-1), with 4 replicates. At 90 days after stakes were prepared, survival and growth variables were evaluated. For both plant materials, significant response was observed after application of ethephon the mother plants, confirming a higher percentage of live cuttings and rooted cuttings. The best results were obtained when herbaceous cuttings were used in both plant materials, which presented higher percentage of live cuttings, sprouts, rooted, as well as higher dry mass of shoots and roots. Under the conditions of this study, it is recommended the use of herbaceous cuttings from matrix plants treated with ethephon for the production of seedlings of elite lineage, and also application of 2000 mg.L-1 of IBA, for production of seedlings of cv. BRS 235 Apodi.